109 Erect Penile Low Intensity Shockwave Therapy (LiSWT): Vascular and Erectile Tissue Health Changes Pre- and Post-Treatment. (1st May 2022) - Uloko, M; Yee, A; Goldstein, S; Goldstein, I
ABSTRACT: Introduction: In 2010, low-intensity shockwave therapy (LiSWT) was first described for used on the flaccid penis as a novel and minimally invasive regenerative treatment for men with ED. A standardized protocol for use of LiSWT either in the flaccid or erect state has not yet been established. Erect penile LiSWT, in contrast to flaccid penile LiSWT, is performed with maximal penile shaft blood volume under conditions of greatest acoustic impedance. This minimizes transfer of shockwave energy though the erectile tissue enabling the greatest uptake of shockwave energy to the erectile tissue. We review our experience with LiSWT during pharmacologic erection. Objective: Assess arterial blood flow and erectile tissue health parameters in ED patients prior to and following erect penile LiSWT to better document the hypothesized vascular/erectile tissue regenerative benefits associated with LiSWT in men with ED. Methods: A retrospective chart review was performed. Prior to LiSWT (Urogold 100 MTS). ED patients underwent a baseline penile Grayscale/Doppler ultrasound (G/DUS) with Grade 3-4/4 erection following appropriate visual/pharmacologic stimulation. A B-mode ultrasound (Aixplorer 15.4 MHz transducer) was then performed at specific settings to avoid reader bias. This included 12 total axial images obtained at proximal, midshaft and distal dorsal penis at a fixed dynamic range of 70 dB with B-mode gain values of increased brightness (45%, 55%, 65%). The fourth image at each axial location was taken at a dynamic range of 49 dB and a B-mode gain value identified as providing the best discrimination between Grayscale black/white. Subsequently, in the erect shaft right/left sagittal planes, cavernosal artery peak systolic velocity (PSV) and end diastolic velocity (EDV) values were obtained. ED patients then underwent 6 erect penile LiSWT treatments over varying intervals. The protocol included: appropriate visual/pharmacologic stimulation to obtain Grade 3-4/4 erection, 600 shocks using a parabolic reflector probe (OP-155), energy flux density 0.13mJ/mm 2, 3 Hz, membrane pressure 3, applied each to dorsal, ventral, right/left lateral erect penile shafts, and right/left erect crura (total shocks 3600, duration of LiSWT ∼ 28 minutes). Patients returning for erect penile LiSWT completed a PGI-I score. Approximately one month after the last erect penile LiSWT, a post-treatment penile G/DUS with Grade 3-4/4 erection was repeated resulting in 24 Grayscale images. Baseline and post-treatment G/DUS were de-identified and read by two experts reaching consensus concerning erectile tissue homogeneity/inhomogeneity where Grayscale (0/3) was consistent with no inhomogeneity; (1/3) mild inhomogeneity (<25% of cross-sectional area revealing hypo- or hyper-echoic regions), (2/3) moderate inhomogeneity (25% - 50%), and (3/3) severe inhomogeneity (>50%), respectively. In addition, PGI-I scores were assessed and compared to ultrasound findings Results: A total of 79 patients (mean age 44 +/- 21, range 19 – 85) met inclusion criteria. A total of 53/79 (67%) had improved erectile tissue homogeneity post-LiSWT from baseline, 10/79 (13%) were unchanged, 15/79 (19%) worsened. Of the 53 patients with improved G/DUS findings, 40/53 patients (75%) rated PGI-I as improved. 37/53 (70%) patients had PSV increase and 18/53 (34%) had EDV decrease. Conclusions: The mechanisms by which erect penile LiSWT improves erectile function, in part, involve enhanced erectile tissue homogeneity, increased cavernosal arterial PSV and decreased EDV. Disclosure: Work supported by industry: no.